From an Existential Vacuum to a Tragic Optimism The Search for Meaning and Presence of God in Modern Literature. - Heavilin, Barbara A. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
From an Existential Vacuum to a Tragic Optimism: The Search for Meaning and the Presence of God in Modern Literature employs a new theoretical approach to critical analysis: Victor Frankl's logotherapy (from the Greek ""logos"" for word or reason and often related to divine wisdom), a unique form of existentialism. On the basis of his observations of the power of human endurance and transcendence - the discovery of meaning even in the midst of harrowing circumstances - Frankl diagnoses the mala...
Table of contents; abbreviations; abbreviations; illustration; preface; acknowledgements; introduction; abbreviations; part i; chapter one; chapter two; chapter three; part ii; chapter four; chapter five; chapter six; part iii; chapter seven; chapter eight; chapter nine; notes; bibliography; index
Description based upon print version of record.
Keywords: God in literature; Literature, Modern -- 20th century -- History and criticism; Meaning (Philosophy) in literature; Religion and literature; God in literature; Meaning (Philosophy) in literature; Religion and literature; BIOGRAPHY & AUTOBIOGRAPHY / Literary; Electronic books